Genome-Wide Approach Identifies Natural Large-Fragment Deletion in ASFV Strains Circulating in Italy During 2023 - Claudia Torresi; Roberta Biccheri; Cesare Cammà; Carmina Gallardo; Maurilia Marcacci; Simona Zoppi; Barbara Secondini; Caterina Riverso; Alejandro Soler; Cristina Casciari; Michela Pela; Elisabetta Rossi; et al. (Pathogens)
African swine fever (ASF), characterized by high mortality rates in infected animals, remains a significant global veterinary and economic concern, due to the widespread distribution of ASF virus (ASFV) genotype II across five continents. In this study, ASFV strains collected in Italy during 2022–2023 from two geographical clusters, North-West (Alessandria) and Calabria, were fully sequenced. In addition, an in vivo experiment in pigs was performed. Complete genomic sequencing of 30 strains revealed large-fragment deletions and translocations. In Alessandria, five samples showed two different deletions in the 5′ genomic region: a ~4340 bp deletion (positions ~9020–13,356 in Georgia 2007/1) in four samples and a 2162 bp deletion (positions 17,837–19,998) in one sample. Another strain showed a truncation of 1950 bp at the 3′ end. In Calabria, strains showed a 5137 bp deletion (positions 10,755–15,891) and ~2 kb truncations in the 3′ region. Two strains showed a translocation from the region 1–2244 to positions 188,631–190,584. In vivo characterization of the deleted strain 22489.4_2312/RC/2023 revealed identical disease progression to the wild-type strain, with severe ASF symptoms in inoculated pigs. This study is the first to report natural deleted strains of ASFV in Italy, revealing unique genomic deletions distinct from those in previously known strains.